Seminar Menulis Artikel Ilmiah: “Menulis Artikel Mulai dari Nol” Bagi Mahasiswa - Rahmatullah Rahmatullah; Pahrudin Pahrudin; Zul Hidayatullah; Lita Bela Ariana (Indonesian Journal of Education and Community Services, 2026)
Writing articles is a crucial issue for university students. Throughout their studies, students are faced with assignments related to scientific articles, ranging from reviewing articles to writing them as assignments or as requirements for graduation. This challenge is a necessity for them, requiring in-depth training. This seminar aims to equip students with the understanding and skills to write effective articles. Eighty-three participants from various universities in East Lombok participated in the seminar. The event took place at Hamzanwadi University, East Lombok. The seminar included material delivery, discussion, and a question-and-answer session. The material was divided into two separate sessions. The first session explained the content of scientific articles, and the second session discussed writing errors and proper publication procedures in target journals. The event went well and smoothly. Participants responded positively, gaining a deeper understanding of article writing. This activity was highly relevant to students' needs. Participants' apprehension about writing was reduced, and their confidence increased. The conclusion of the event was an increase in participants' understanding and skills of writing scientific articles, from the initial writing process to the publication process.